The Impact of Digital Technology on Various Traditional Theaters: An Examination of the Sociology of Arts - Sahid, Nur; Syafii, A.S. Hardy; Sathotho, Surya Farid; Yuliadi, Koes; Purwanto, Purwanto (Universitas Negeri Semarang, 2025)
The advancement of digital technology has engendered substantial transformations across various dimensions of life, particularly within the realm of traditional performing arts. In Indonesia, traditional art forms such as ketoprak, drama gong, and wayang purwa are currently undergoing significant changes in terms of production, presentation, and consumption in the digital age. This article explores the effects of digitization on these three art forms through the lens of Janet Wolff’s sociology of art framework. According to Wolff’s perspective, artworks are perceived as the outcome of the interplay among diverse social, economic, and cultural factors, with digital technology playing a crucial role in redefining the modern landscape of performing arts. The research findings indicate that digitalization facilitates the expansion of engagement with global audiences while simultaneously preserving local cultural values. Nevertheless, challenges manifest in the form of cultural gentrification, which threatens the erosion of indigenous aspects of tradition. Furthermore, this article offers recommendations for artists to harness technology in order to produce relevant artworks in the context of globalization, without compromising their cultural identity.